Cells at the Edge: The Dentin–Bone Interface in Zebrafish Teeth - Rosa, Joana T.; Witten, Paul Eckhard; Huysseune, Ann (Frontiers in Physiology, 2021)
Bone-producing osteoblasts and dentin-producing odontoblasts are closely related cell types, a result from their shared evolutionary history in the ancient dermal skeleton. In mammals, the two cell types can be distinguished based on histological characters and the cells’ position in the pulp cavity or in the tripartite periodontal complex. Different from mammals, teleost fish feature a broad diversity in tooth attachment modes, ranging from fibrous attachment to firm ankylosis to the underlying bone. The connection between dentin and jaw bone is often mediated by a collar of mineralized tissue, a part of the dental unit that has been termed “bone of attachment”. Its nature (bone, dentin, or an intermediate tissue type) is still debated. Likewise, there is a debate about the nature of the cells secreting this tissue: osteoblasts, odontoblasts, or yet another (intermediate) type of scleroblast. Here, we use expression of the P/Q rich secretory calcium-binding phosphoprotein 5 (scpp5) to characterize the cells lining the so-called bone of attachment in the zebrafish dentition. scpp5 is expressed in late cytodifferentiation stage odontoblasts but not in the cells depositing the “bone of attachment”. nor in bona fide osteoblasts lining the supporting pharyngeal jaw bone. Together with the presence of the osteoblast marker Zns-5, and the absence of covering epithelium, this links the cells depositing the “bone of attachment” to osteoblasts rather than to odontoblasts. The presence of dentinal tubule-like cell extensions and the near absence of osteocytes, nevertheless distinguishes the “bone of attachment” from true bone. These results suggest that the “bone of attachment” in zebrafish has characters intermediate between bone and dentin, and, as a tissue, is better termed “dentinous bone”. In other teleosts, the tissue may adopt different properties. The data furthermore support the view that these two tissues are part of a continuum of mineralized tissues. Expression of scpp5 can be a valuable tool to investigate how differentiation pathways diverge between osteoblasts and odontoblasts in teleost models and help resolving the evolutionary history of tooth attachment structures in actinopterygians.